Cytokine profiles in serum of patients with oral lichen planus - NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2012)
Objective: Oral lichen planus (OLP) is a chronic inflammatory disorder of oral mucosa, which represents T-cell-mediated autoimmune diseases. The inflammatory response in OLP is characterized by the accumulation and expansion of T-helper 1 (Th1) lymphocytes. Several lines of evidence have suggested that a complex cytokine network plays an important role in the exacerbation and perpetuation of OLP. The aim of this study was to evaluate Th1 and T-helper 2 (Th2) cytokine profile in serum of patients with OLP in comparison to healthy controls. Methods: Thirty patients with OLP, and 30 healthy controls participated in the study. Tumor necrosis factor (TNF)-alpha, interferon (IFN)-gamma, interleukin (IL)-2, IL-4, IL-5 and IL-10 levels have been measured in flow cytometry by bead based cytokine measurement. Results: Although no statistical differences were observed in the serum levels of TNF-alpha, IFN-gamma, IL-5 and IL-4 between OLP patients and controls (p > 0.05), there were statistically significant differences in the serum levels of IL-2 and IL-10 (p < 0.05 and p < 0.01, respectively). A significantly decreased tendency towards the levels of IL-2 were observed in OLP patients when compared to controls (p < 0.05), and the mean level of IL-10 in serum increased remarkably in the OLP patients than those in the controls (p < 0.01). Conclusions: The finding of higher serum levels of IL-10 in patients in presence of low serum IL-2 levels, shows us that there is a dominance of Th2 response. This makes us think that there is a change in Th1/Th2 balance. Dominance of the Th2 response may indicate that OLP could be a result of a delayed type hypersensitivity. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Oral lichen planus; Cytokine; T helper 1; T helper 2; NECROSIS-FACTOR-ALPHA; TNF-ALPHA; T-CELLS; IL-10; INTERLEUKIN-10; PATHOGENESIS; EXPRESSION; TH1